Magnanakaw - Pascual, Chuckberry J. (Philippine humanities review = Rebyu ng Arte at Literatura ng Pilipinas.)
"It is in pursuing a petty thief that this protagonist unexpectedly finds answers to a number of queries he has about life in general. The deceptively simple story actually presents other ways of looking at crime, theft in particular, class, gender, and violence, and how all these overdetermine an individual's position in society." -- Introduction